2017
DOI: 10.1002/eap.1539
|View full text |Cite
|
Sign up to set email alerts
|

An ecosystem services approach to the ecological effects of salvage logging: valuation of seed dispersal

Abstract: Abstract. Forest disturbances diminish ecosystem services and boost disservices. Because post-disturbance management intends to recover the greatest possible value, selling timber often prevails over other considerations. Ecological research has shown diverse effects of salvage logging, yet such research has focused on the biophysical component of post-disturbance ecosystems and lacks the link with human well-being. Here we bridge that gap under the ecosystem services framework by assessing the impact of post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Salvage logging—the removal of trees after natural disturbance—is often conducted for various reasons, often with little outcry from the public (Lindenmayer, Burton, & Franklin, ). However, the increasing frequency, severity, and extent of natural disturbances (Diffenbaugh & Field, ) over recent decades are triggering unprecedented levels of salvage logging in places where logging never occurred previously (such as ostensibly protected areas; Müller, Jarzabek‐Müller, & Bussler, ; Schiermeier, ) and at unparalleled levels of intensity and extent (Leverkus & Castro, ; Thom & Seidl, ).…”
Section: Introductionmentioning
confidence: 99%
“…Salvage logging—the removal of trees after natural disturbance—is often conducted for various reasons, often with little outcry from the public (Lindenmayer, Burton, & Franklin, ). However, the increasing frequency, severity, and extent of natural disturbances (Diffenbaugh & Field, ) over recent decades are triggering unprecedented levels of salvage logging in places where logging never occurred previously (such as ostensibly protected areas; Müller, Jarzabek‐Müller, & Bussler, ; Schiermeier, ) and at unparalleled levels of intensity and extent (Leverkus & Castro, ; Thom & Seidl, ).…”
Section: Introductionmentioning
confidence: 99%
“…A potentially severe form of perturbation in forests is salvage logging in which trees damaged by natural disturbance are harvested in an attempt to recover some of their economic value (Cobb et al., ; Fraver, Dodds, Kenefic, Seymour, & Sypitkowski, ; Leverkus & Castro, ). Salvage logging is widespread and its use is increasing (Thorn et al., ), likely as a result of the increase in large‐scale intensive natural disturbances globally (Seidl, Schelhaas, Rammer, & Verkerk, ).…”
Section: Introductionmentioning
confidence: 99%
“…In short, the role of snags and other CWD as biological legacies that promote biodiversity, regeneration, and ecosystem functioning has been increasingly demonstrated by studies performed mostly in the last couple of decades. These studies overall provide evidence for the need of retaining part of these structures as key elements for habitat restoration and biodiversity conservation [3,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for conducting SL are diverse, but are largely related either to the recovery of economic capital still available in the remaining wood soon after the disturbance, or to facilitate future restoration or reforestation [19,20]. Nonetheless, this management action has been sharply criticized in the last two decades, and a growing number of studies have showed that salvage logging may seriously compromise ecosystem regeneration [3][4][5][6][7][8][9][10][11][12][13][14][15]21,22]. It is becoming increasingly clear that the negative effect of SL is related to its impact on habitat structure and components, which is linked primarily to the amount of biomass removed and the simplification of habitat structure [9,10,12,23].…”
Section: Introductionmentioning
confidence: 99%